On Subject & Negative Positioning in Spanish - Sobin, Nicholas; Mazzaro, Natalia (Borealis – An International Journal of Hispanic Linguistics, 2026)
Negative English sentences (‘Mary does not want apples’) suggest that the order of key elements is TP–NegP–VP.  However, negative Spanish sentences (‘María no quiere manzanas’) suggest the order Subject–NegP–Tense/VP.  Regarding subject positioning, some claim that subjects in Spanish are located in Rizzi’s (1997) Split CP.  Others maintain that Spanish subjects are located in SpecTP or SpecAgrSP.  In either case, utilizing Pollock’s (1989) split IP proposal, locating Neg(P) between AgrSP and TenseP would result in the placement of Neg(P) above TenseP, as Spanish seems to display.  Thus, Spanish and English would appear to differ in the structure underlying negative sentences.  Further, such accounts often involve additional structural elaboration, though minimalist syntax emphasizes structural simplicity.  We propose an analysis of negative sentences in Spanish based on top–down syntax.  In both English and Spanish, there is no NegP.  Neg is a component of T.  The creation of both negative sentences in Spanish and of expanded (uncontracted) negative sentences in English involves internal merger downward of the (verb)/T/Neg head.  In Spanish, the Neg portion of the higher copy of this head (verb/T/Neg) is spelled out as no, and the lower copy (verb/T/Neg) is spelled out as the finite verb.  In English, the opposite is true. The higher copy (T/Neg) is spelled out as T, and the lower copy(T/Neg) is spelled out as not.  That is, Spanish and English negative sentences involve basically the same underlying structure, and the difference between them reduces to a difference in spell out conventions.
Keywords: Negative sentences; top–down syntax; spell out; complex lexical items; NegP; negative concord; Spanish